2022
DOI: 10.5194/hess-26-91-2022
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: High-accuracy weighing micro-lysimeter system for long-term measurements of non-rainfall water inputs to grasslands

Abstract: Abstract. Non-rainfall water (NRW), defined here as dew, hoar frost, fog, rime, and water vapour adsorption, might be a relevant water source for ecosystems, especially during summer drought periods. These water inputs are often not considered in ecohydrological studies, because water amounts of NRW events are rather small and therefore difficult to measure. Here we present a novel micro-lysimeter (ML) system and its application which allows us to quantify very small water inputs from NRW during rain-free peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…However, large lysimeters might not allow easily to observe small scale variation induced by grassland canopy. Further micro lysimeters in temperate climate needs to be controlled for how natural canopy and root growth might be altered due to the restricted root structure (Riedl et al, 2022) since, as we observed, the amount of net precipitation components, thereby interception, changes through seasonal plant development.…”
Section: Validation Of Net Precipitation Measurements Based On Soil W...mentioning
confidence: 92%
“…However, large lysimeters might not allow easily to observe small scale variation induced by grassland canopy. Further micro lysimeters in temperate climate needs to be controlled for how natural canopy and root growth might be altered due to the restricted root structure (Riedl et al, 2022) since, as we observed, the amount of net precipitation components, thereby interception, changes through seasonal plant development.…”
Section: Validation Of Net Precipitation Measurements Based On Soil W...mentioning
confidence: 92%
“…Since clear-sky conditions and the amount of humidity present in the air is a key factor for both dew and radiation fog formation, their distinction is challenging. Measurements from visibility sensors are therefore used in addition to RH t to classify fog unambiguously (e.g., Feigenwinter et al, 2020;Riedl et al, 2022). Given that at the experimental site visibility sensors are not available, we use LW radiation to benchmark fog occurrence in our analysis.…”
Section: Identification Of Fog Conditions and Their Separation From Dewmentioning
confidence: 99%
“…But current research that is quantifying such ratios is too scarce for generalization (Y. . Some studies, therefore, do not distinguish between fog and dew (Groh et al, 2018) or add a category of combined dew and fog (Riedl et al, 2022). Disentangling individual NRW fluxes is nevertheless important because of different respective (i) controlling factors and (ii) implications for the ecosystem.…”
Section: Distinguishing Non-rainfall Water Formationmentioning
confidence: 99%
See 2 more Smart Citations